Carmen Miranda entre os desejos de duas nações: cultura de massas, performatividade e cumplicidade subversiva em sua trajetória - Balieiro, Fernando de Figueiredo (2014)
In 1939, Carmen Miranda was a consecrated singer in Brazil, in her career on the radio broadcasting as well as theatres and casinos. As a national idol she went to the United States under a contract for a revue on Broadway. Her new career in the United States was seen by Brazilians as a diplomatic mission and she was required to represent her nation and introduce the national rhythm samba to the North-American audiences. At that time, she performed the national identity which was remodeled through the mass culture national dynamics, integrating popular and afro-Brazilian elements, but also filtering them in order to produce an image based on whiteness. In this way, the white artist, remembered for her remarkable green eyes and attuned to the Hollywoodian fashion, featured the Baiana character, a Brazilian national type which referred to a black woman. In her international career, however, she became the new representation of Latin America in the midst of the Good Neighbor Policy period. Carrying her stylized Baianas dressings, Miranda evoked a happy, cheerful, sensual, exuberantly representation of Latin America, offering the opportunity to escapism during the World War II. From the radio broadcasting to the Hollywood cinema, and also participating in some TV shows, Carmen Miranda was part of a process in which the Brazilian national identity came to be produced through the mass culture involving national and international creations. Through the concept of performativity, this thesis explores how Carmen Miranda created new symbolical senses about the national identity and Latin American representations in a form of complicity, with consolidated meanings based on coloniality , considering both national and international dimensions. Because of her path (closely related to the Brazilian popular culture), Carmen reproduced the cultural meanings involved in her representations through three constitutive elements: humor, exaggeration and caricature. These characteristics, alongside with self-parody and irony, enabled some kinds of audiences to read her performances as subversive in a sense that she was destabilizing the comprehension of identity as essence, and, at the same time, challenging social constructed hierarchies. These features allowed her to be appropriated as a camp icon, in the United States, and in a carnivalesque way, in Brazil.